Is Tillandsia capillaris an efficient bioindicator of atmospheric metal and metalloid deposition? Insights from five months of monitoring in an urban mining area. (August 2016) - Schreck, Eva; Sarret, Géraldine; Oliva, Priscia; Calas, Aude; Sobanska, Sophie; Guédron, Stéphane; Barraza, Fiorella; Point, David; Huayta, Carlos; Couture, Raoul-Marie; Prunier, Jonathan; Henry, Manuel; et al.
Abstract : Graphical abstract: Highlights: T. capillaris and passive filters monitor atmospheric deposition of metal(loid)s. Metal(loid)s dynamics and speciation change in T. capillaris after use as air biomonitor. After a five months exposure, data from plants and passive filters are not equivalent. X-ray spectroscopy evidenced of chemical transformation inside the plant (Pb and As). Abstract: Atmospheric pollution in megacities has a major impact on human health and environmental quality. Air quality bioindicators may have some advantages over standard devices such as impactors or filters. In this study we evaluated the reliability of Tillandsia sp. versus passive filters for monitoring the atmospheric deposition of metal(loid)s in an area affected by anthropogenic activities. We aimed to gain insight into the composition and origin of atmospheric particles and their fate after deposition on the plant. Three zones with different contamination levels were monitored for five months in 2012. For the highly contaminated area, a linear increase in metal(loïd) accumulation was found in passive filters, whereas for transplanted Tillandsia capillaris the increase was almost linear for As, Cd, Hg, and Sn, but not for Ag, Pb, Sb, and Zn. For the moderately contaminated zone, the results showed that the exposure time was not sufficient for metal(loid) concentrations to increase in either the plants or filters. However, natural specimens provided some indications of the levels of metal contamination. Metal particles were observed on the plant surface and also in the central disc underneath tillandsia trichomes, suggesting that this is a possible pathway for metals to enter the plant. X-ray absorption spectroscopy demonstrated chemical transformation for Pb and As, both in filters and plants. For Pb, sorbed Pb and/or cell wall complexes were identified in the plants. No As III -S species, indicative of As detoxification, were identified in the plant. Arsenic was oxidized from As III to As V in both plants and filters. Thus, in the present study, passive filters proved more reliable than T. capillaris transplants, although natural specimens provided some insights into local contamination. Particulate contaminants underwent chemical transformation after being trapped in the plant, but there was no clear evidence of internalization and detoxification.